Implementasi Model Pembelajaran PBL Berbasis HOTS Pada Pembelajaran IPA - Budi Lestari (Program Studi PGSD STKIP PGRI Banjarmasin, 2021)
This paper presents how the model is Problem Based Learning (PBL)applied to the material (IPA) in grade IV Elementary School. PBL is a learning approach that uses real-world problems as a context for students to optimize students' thinking skills through a systematic group or team work process, so that students can empower, hone, test, and develop their thinking skills on an ongoing basis. The PBL learning model also provides opportunities for students to stimulate higher-order thinking. The steps of the learning model have 5 stages, namely the learning model. the PBL lesson implementation phase in the process has five phases, the first 1) The student orientation phase on the problems contained in the PBL, 2) The stage of organizing students to learn, 3) The stage of guiding individual and group investigations, 4) The stage of developing and presenting the results, and 5) The stage of analyzing and evaluating the problem solving process.